Target Detection Using Learning Methods - Sahnoon, Mohammad Moufeed (2017)
A Master of Science thesis in Electrical Engineering by Mohammad Moufeed Sahnoon entitled, "Target Detection Using Learning Methods," submitted in June 2017. Thesis advisor is Dr. Khaled Assaleh and thesis co-advisors are Dr. Usman Tariq and Dr. Hasan Mir. Soft and hard copy available.